Therapeutic strenght in funeral ceremonies - Juan Carlos Delgado Antolín (Universidad de Alicante, 2012)
Care is always provided within cultural boundaries and those precise cultural boundaries will result in the type of care that should be singled appropriate to circumstances. The present study approaches a reflection on the topic ceremonies inherent in all sorts of cultures and their paramount importance in the evolution of every human being. If the different rites or ceremonies along a life span have a deep impact on the individual as of integrating needs to be fulfilled in that particular society, perhaps the funeral rite or ceremony is the only one where the human being, the closest object of the rite, the physical entity the rite is directed to, does not receive the consequences which on the contrary sit upon relatives and friends. The therapeutic consequences of that precise rite or ceremony remain upon those who perform it but not upon 'the receiver' himself (as it is for the rest of life ceremonies). 'He' is present, but 'he' is no more a human being, 'he' does not exist. Finally, two might be the causes why the rite or ceremony could be somewhat therapeutic for those people who perform it. The ruling character 'according to the rules' and 'according to the cultural environment' where they be performed.